Results from the National Examination before and after 2012-2013 Education Reforms: Lessons and Perspectives - Norbert Niyitanga (Raja Zulkarnain Education Foundation, 2026)
This study examined comparatively scores in eight National Examination of English done upon the completion of Junior high school level and the students’ scores in them. The examinations concerned are four of grade 9 at Basic school and the others four of the former education system. In conducting it, we sought to answer two research questions. While the first was set to understand students’ performance in the first four editions in basic education system compared to their counterparts’ performance in the last four editions in the former system, the second intended to draw lessons from the two categories of students. Document/content analysis was used for data collection. The collected data were the scores in eight national examinations and they were analyzed quantitatively. Microsoft Excel and SPSS were used to this end. After analyzing the collected data, it was found that students evolving in basic education system perform better than their counterparts in the former system. However, it was remarked that their performance generally is low, which calls for better strategies to improve it. It was, therefore, suggested that designing more adequate National Examinations and capitalizing results in them, redirecting the teaching to reflect the National Examination, as well as changing students’ attitudes and the learning environment would help to improve students’ performance in the National Examination.